KARAKTERISTIK PENYULUH DALAM PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA INFORMASI PERTANIAN - Lutfi Humaidi; Aida Vitayala S Hubeis; Herien Puspitawati; Oos E M Anwas (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
This research was an explanatory research that explains the phenomena that influence the social media utilization as agricultural information media. This research was conducted in Riau Islands Province from May to September 2019. The research sample was determined by census method. The total number of 90 Civil Servants (PNS) and Agricultural Extension Workers Relief Personnel (THL-TBPP), all of which were used as respondents in this research. The research variables consist of independent variables, namely the characteristics of extension agents (X), and the dependent variable, namely the use of social media (Y). Data collection methods in this study used questionnaires, interviews, and documentation. Analysis of the data used: descriptive analysis, and PLS analysis with SmartPLS 3.0 software. The results showed that the characteristics of extension workers were in the low category, while the use of social media was in the medium category. Utilization of social media that is reflected through facebook, whatsapp and youtube is influenced by the characteristics of instructors that are reflected through age, experience as counselors and cosmopolitan.